Business @ the Speed of Thought: Using a Digital Nervous System - Bill Gates; GATES (Bill); HEMINGWAY (Collins) (New York Warner Books, 1999)
In his new book, Microsoft chairman and CEO Bill Gates discusses how technology can help run businesses better today and how it will transform the nature of business in the near future. Gates stresses the need for managers to view technology not as overhead but as a strategic asset, and offers detailed examples from Microsoft, GM, Dell, and many other successful companies. Companion Web site.
Keywords: Business enterprises--Computer networks; Business enterprises--Communication systems; Information resources management; Information technology--Managemen; Digital communications; Communication and technology; Business enterprises--Technological innovations